Petri Nets and Bisimulations - Nielsen, Mogens; Winskel, Glynn (BRICS Report Series, 1995)
Several categorical relationships (adjunctions) between models for concurrency have been established, allowing the translation of concepts and properties from one model to another. A central example is a coreflection between Petri nets and asynchronous transition systems. The purpose of the present paper is to illustrate the use of such relationships by transferring to Petri nets a general concept of bisimulation.